Summary report of the British Academy project on 'Forced Migration, Religious Diplomacy and Human Security in the Eastern Orthodox World'. Issue 1 (2nd January 2019) - Leustean, Lucian N.
ABSTRACT: This review article provides an overview of the British Academy Project on 'Forced Migration, Religious Diplomacy and Human Security in the Eastern Orthodox World' (January–December 2018), research questions, methodology, main findings and policy recommendations. The project compared the ways in which religious communities engaged with forced displaced populations in Eastern Europe and former Soviet states, with a particular focus on Serbia and Ukraine, collected a dataset on 'Eastern Orthodoxy and Human Security' and organised two workshops in Belgrade and Kyiv.